ROBOTIC PROCESS AUTOMATION IN HEALTHCARE: REVOLUTIONIZING PATIENT CARE AND ADMINISTRATION - Dr. Erik Johansson (Modern American Journals, 2025)
Robotic Process Automation (RPA) is rapidly emerging as a transformative technology in healthcare, automating administrative processes and enhancing clinical care. RPA's application in healthcare is centered on streamlining tasks such as billing, scheduling, insurance claims, and data entry, reducing operational costs and minimizing errors. In clinical settings, RPA is also employed in robotic-assisted surgeries and remote patient monitoring. This paper explores the impact of RPA in both administrative and clinical domains, evaluates the benefits, challenges, and limitations of its adoption, and suggests strategies for integrating RPA into healthcare organizations. The findings underscore the potential of RPA to improve patient outcomes, enhance efficiency, and reduce operational costs in healthcare settings.
Keywords: Robotic Process Automation, Healthcare Automation, Patient Care, Administrative Efficiency, Healthcare Robotics, RPA in Clinical Settings, Process Improvement, AI in Healthcare.